RISK ASSESSMENT OF INVESTMENT PORTFOLIO - Dubrovin, V. I.; Liovkin, V. M. (Radio Electronics, Computer Science, Control, 2010)
Investment portfolio optimization approaches (proposed in the works by Markowitz, Sharpe and Value-at-Risk methodology, fuzzy approach based on possibility theory) were analyzed. Risk assessment tools (based on standard, semiquadratic and median semi-quadratic deviation, critical values of profitability), used in these methods, were considered in details and their main shortcomings and advantages were detected. Advices for investment portfolio optimization methods choice (and for risk assessment accordingly) were given under special conditions.